A new type of nest in the genus Quindina (Opiliones: Nomoclastidae) with hypotheses about its origin and a new species for Colombia - Lancheros, Héctor (2024)
Introduction: Parental care is a phenomenon that has been recorded for several clades of the order Opiliones, but nest building has only been reported in the Neotropical genus Quindina Roewer, 1914 (Nomoclastidae). Objective: To describe a new type of nest used in parental care by a new species of Quindina and determine its placement in the phylogenetic tree of the genus, to propose hypotheses about the origin of the two types of nests reported so far. Methods: Specimens and nests were collected in La Calera, Cundinamarca, Colombia. Observations of parental care were made both in the field and in terrariums. A new species was described based on somatic characters and penis structure. A phylogenetic analysis was carried out, consensus methods with equal weights, implicit weighting, and successive weighting were used. Results: We describe a new case of parental care with a new type of disc-shaped nest, which we call "pendular disc nest". The nest is built by males of Quindina pendula sp. nov.; this species can be recognized externally by the absence of white spots, the presence of a mushroom-shaped set of patches in the middle part of the prosoma, and the presence of a dark yellow background around most of the tubercles. Results of the phylogenetic analysis showed Q. pendula sp. nov. is sister to all Quindina species except Quindina marginata. Based on the tree, obtained by successive weighting, seven phylogenetic hypotheses, related to the possible origin of the two types of nests recorded in the genus Quindina, were proposed. Conclusions: This study presents a new case of egg guarding and the building of nests in arthropods, which is not very common in nature.